Pharmacological treatment of lupus erythematosus systemicus: new directions including experimental methods - Samborski, Włodzimierz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
A new understanding of the pathogenesis of autoimmunity gives other options for treatment of lupus erythematosus systemicus including the novel immunosuppressive agents and target-specific biological therapies.